Bright‐Line Fever: Simple Legal Rules and Complex Property Customs among the Fataluku of East Timor. Issue 2 (1st May 2013) - Fitzpatrick, Daniel; McWilliam, Andrew
<x xml:space="preserve">Abstract</x> Recent law and economics scholarship has revived a debate on bright‐line rules in property theory. Economic analysis asserts a baseline preference for bright‐line property rules because of the information costs if "all the world" had to understand a range of permitted uses, or deal with multiple interest holders in a resource. A baseline preference for bright‐line rules of property arises from the cost of communicating information: all else being equal, complex rules suit smaller audiences (e.g., contracting parties) and simple rules suit large audiences (e.g., property transactors, violators, and enforcers). This article explores the circumstances in which a simple rule, purportedly for a large audience, takes on interpretive complexity as it traverses specialized audience segments. The argument draws on two heuristic strands of recent sociolegal scholarship: systems theory notions of autopoiesis, and concepts of negotiability in plural property relations. The potential for complex interpretations of simple legal rules is illustrated through a case study of the Fataluku language group in the district of Lautem, East Timor.